War and empire : the expansion of Britain, 1790-1830 - Collins, Bruce (Routledge, 2014)
The years 1790 to 1830 saw Britain engage in an extensive period of war-waging and empire-building which transformed its position as an imperial state, established its reputation as a distinctive military power and secured naval preeminence.Despite this apparent success, Britain did not become a world super power in the conventional sense. Instead, as Professor Collins demonstrates, it operated as an enclave power, influencing or dominating many regions of the world without ever asserting global hegemony. Even in the 1820s, Britain still had to fight to maintain influence, and sometimes strugg.